PENGARUH DANA PIHAK KETIGA, LDR, ROA, DAN ROE TERHADAP JUMLAH PENYALURAN KREDIT - Intan Yunnyarti Permatasari; Agus Endro Suwarno (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of Third Party Funds, LDR, ROA, and ROE on the amount of lending in all commercial banks listed on the IDX for the period 2013-2018. The population in this study were all commercial banks listed on the IDX for the period 2013-2018. The data collection technique in this study used a documentation study. To analyze the research using the Multiple Linear Regression analysis method assisted by the SPSS 17 program. The results of the study prove that third party funds, LDR, ROA and ROE simultaneously affect the amount of credit disbursement. the results of the coefficient of determination test (R2) obtained a value of 69.9% of the independent variables affect the distribution of commercial bank loans and the remaining 30.1% is influenced by other variables not examined in this study.